2015
DOI: 10.1007/s13346-015-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of biomineralized scaffold-directed osteogenic differentiation of human embryonic and mesenchymal stem cells

Abstract: Human pluripotent stem cells such as embryonic stem cells (hESCs) and multipotent stem cells like mesenchymal stem cells (hMSCs) hold great promise as potential cell sources for bone tissue regeneration. Comparing the in vivo osteogenesis of hESCs and hMSCs by biomaterial-based cues provides insight into the differentiation kinetics of these cells as well as their potential to contribute to bone tissue repair in vivo. Here, we compared in vivo osteogenic differentiation of hESCs and hMSCs within osteoinductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Cell-based approaches utilizing mesenchymal stem cells (MSCs) are under investigation for bone repair of atrophic nonunions, craniomaxillofacial defect repair, and hard palate reconstruction. [3] MSCs are multipotent cells that, among other phenotypes, can participate in bone formation directly by differentiating toward the osteoblastic phenotype [46] or indirectly by secreting paracrine acting trophic factors that stimulate angiogenesis and regulate local inflammation. [710] Regardless of their contribution, long-term survival and engraftment of MSCs to defect sites is poor, [11, 12] drastically decreasing the therapeutic potential of MSC-based treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based approaches utilizing mesenchymal stem cells (MSCs) are under investigation for bone repair of atrophic nonunions, craniomaxillofacial defect repair, and hard palate reconstruction. [3] MSCs are multipotent cells that, among other phenotypes, can participate in bone formation directly by differentiating toward the osteoblastic phenotype [46] or indirectly by secreting paracrine acting trophic factors that stimulate angiogenesis and regulate local inflammation. [710] Regardless of their contribution, long-term survival and engraftment of MSCs to defect sites is poor, [11, 12] drastically decreasing the therapeutic potential of MSC-based treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our studies showed that mineralized biomaterials containing calcium phosphate minerals assist osteogenic differentiation of hESCs and hiPSCs in growth medium devoid of any osteogenic inducing soluble factors (58) . This finding suggests that the sole use of mineralized materials is sufficient to direct osteogenic commitment of hPSCs to form 3D bone tissues both in vitro and in vivo .…”
Section: Biomaterials Assisted 3d Tissue Formation Through Hpsc Difmentioning
confidence: 71%
“…In addition to supporting differentiation, these mineralized biomaterials (e.g. Mineralized Polyethylene (glycol) Diacrylate) formed vascularized bone tissue when implanted in vivo (58) .…”
Section: Biomaterials Assisted 3d Tissue Formation Through Hpsc Difmentioning
confidence: 99%
“…Here, scaffolds and various biomaterials have provided an invaluable tool for bone tissue engineering as they can enable a greater level of control over form and structure, and can also be supplemented with osteoinductive agents. Mineralized tissue formed by differentiated PSCs has been shown using various different scaffold materials [93,[124][125][126][127]. In these studies, the engineered tissue was subcutaneously implanted in animal models and in vivo mineralization capacity was evaluated; however, there is a lack of studies that have investigated the in vivo reparative effects of the PSC-derived engineered tissue.…”
Section: Adipogenesis Via Addition Of Growth Factorsmentioning
confidence: 99%